Differences in photosystem II activity and carbon allocation during photomixotrophic growth in distinct wild-type strains of Synechocystis sp. PCC 6803 - Huokko, Tuomas; Sporre, Emil; Koch, Bradley; Patil, Priyanka Pradeep; Wey, Laura; Nikkanen, Lauri; Napaumpaiporn, Pornpan; Virtanen, Olli; Hubácek, Michal; Kulik, Natalia; Komenda, Josef; Hudson, Elton; et al. (Wiley, 2026)
The regulation of photosynthetic electron transport during photomixotrophic growth in cyanobacteria remains incompletely understood. In this study, we characterized four wild-type strains (WT 1–4) of Synechocystis sp. PCC 6803 and observed distinct strain-specific differences in photosystem II (PSII) function under photomixotrophic conditions. Specifically, WT 1 and WT 2 exhibited near-complete inhibition of electron transfer from QA− to QB following approximately 3 days of glucose supplementation, possibly mediated by binding of the small PSII-associated protein, Psb28-2, and resulting in a metabolic shift toward photoheterotrophy. Observed electron transport blockage was associated with changes in the abundances of various photosynthetic proteins. However, the structural integrity of both Photosystems appeared to be largely preserved. Such stabilization may be driven by a transient downregulation of linear electron transport to prevent overreduction of the electron transport chain under photomixotrophy. In contrast, WT 3 and WT 4 maintained photomixotrophic growth throughout the experiment but exhibited slower growth rates than WT 1 and WT 2. Although glucose uptake was slower in WT 1 and WT 2, both strains accumulated more glycogen than WT 3 and WT 4, suggesting divergent regulation of carbon allocation and storage metabolism. Together, these findings highlight the capacity of cyanobacterial strains to deploy distinct metabolic strategies to optimize photosynthetic function, carbon assimilation, and energy storage under photomixotrophic conditions.